Penggunaan Asap Cair dari Tandan Kosong Kelapa Sawit untuk Pengendalian Jamur Phytophthora citrophthora secara In Vitro - Hasan Oramahi; Elvi Rusmiyanto; Kustiati Kustiati (Fakultas Biologi | Universitas Jenderal Soedirman, 2021)
Efficacy of wood vinegar produced from empty fruit bunches (EFB) against Phytophthora citrophthora fungus was evaluated. The objective of the present work is to to evaluate antifungal properties of wood vinegar from EFB against P. citrophthora fungus. Three kinds of wood vinegar were used three temperatures i.e. 350, 400 and 450 °C. Efficacy of wood vinegar from EFB for antifungal is a factorial 3 by 4 in a completely randomized design; the first factor was pyrolysis temperature of wood vinegar from EFB (350, 400, and 450 °C) and the second factor was treatment of concentration of wood vinegar from EFB (0, 0.5, 1.0, and 1.5 %, v/v). The results showed that pyrolysis temperature effect of wood vinegar from EFB and concentration of wood vinegar were significantly different for inhibition of fungal growth. The highest inhibition was on wood vinegar for EFB with temperature pyrolysis of 450 °C and concentration of wood vinegar of 1% with average value of 100%.